Gambaran Tingkat Pengetahuan Trauma Mata pada Mahasiswa Kepaniteraan Klinik FK UKRIDA - SANTI ANUGRAHSARI; ADHE WILLIAM FANGGIDAE; MAWAR; MUTIARA NOVARINDA ISKAYATI PUTRI; TASYA NADHIRATUL HUSNA; THOMAS AQUINAS MICHI ALVIYANTO; TIARA AGUSTINA (HANG TUAH MEDICAL JOURNAL, 2023)
Abstract Introduction: Eye trauma is one of the causes of visual impairment and blindness that occurs due to intentional or unintentional actions. Trauma to the eye requires proper treatment to prevent the occurrence of more severe complications that will lead to blindness. Methods: This research is a descriptive study with a cross sectional study design. The research will be conducted at the KOJA Regional General Hospital in April – May 2022 with the sample being clerks who meet the inclusion criteria. Results: Clinical clerkship students aged <25 years, have a good level of knowledge 48.6%. Meanwhile, clinical clerkship students aged 25-30 years have a good level of knowledge of 57.7%. And clinical clerkship students aged >30 years have a good level of knowledge of 100%. Meanwhile, clinical clerkship students who attended less than 3 stations, had a sufficient level of knowledge of 56.3%. Meanwhile, clinical clerkship students who participated in more than 3 stations, had a good level of knowledge of 58.3%. Conclusion: Most of the clinical clerkship students of UKRIDA FK have a good level of knowledge about eye trauma at Koja Hospital. Keywords : eye trauma, level of knowledge, clinical clerkship students